Mali : Staff Report for the 2001 Article IV Consultation, Third Review Under the Poverty Reduction and Growth Facility, Third Annual Program, and Request for Modification of Performance Criteria. (IMF Staff Country Reports; Country Report, 2002)
This paper examines Mali's 2001 Article IV Consultation, Third Review Under the Poverty Reduction and Growth Facility (PRGF), Third Annual Program, and Request for Modification of Performance Criteria. Program implementation to date has been satisfactory, with all quantitative performance criteria and benchmarks observed through end-July 2001. For the last quarter of 2001, a shortfall is envisaged in program financing, and the bulk of expected budgetary assistance will be disbursed at the end of 2001.